2019 International Conference on Robotics and Automation (ICRA) 2019
DOI: 10.1109/icra.2019.8793976
|View full text |Cite
|
Sign up to set email alerts
|

Robotics Education and Research at Scale: A Remotely Accessible Robotics Development Platform

Abstract: This paper introduces the KUKA Robot Learning Lab at KIT -a remotely accessible robotics testbed. The motivation behind the laboratory is to make state-of-the-art industrial lightweight robots more accessible for education and research. Such expensive hardware is usually not available to students or less privileged researchers to conduct experiments. This paper describes the design and operation of the Robot Learning Lab and discusses the challenges that one faces when making experimental robot cells remotely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Gladly, this approach also gives room to students already accustomed to Arduino programming and gives them the flexibility to write their own Arduino software. Especially for students without any programming or control background, a graphic user interface (GUI) program 6 has been developed. The GPLv3 frontend, shown in Fig.…”
Section: Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Gladly, this approach also gives room to students already accustomed to Arduino programming and gives them the flexibility to write their own Arduino software. Especially for students without any programming or control background, a graphic user interface (GUI) program 6 has been developed. The GPLv3 frontend, shown in Fig.…”
Section: Programmingmentioning
confidence: 99%
“…Given the constant evolution of those robotic systems, many groups have identified that the costs of state-of-the-art manipulators with multiple degrees of freedom (DoFs) are prohibitive for many research groups [5], [6]. This has been addressed in part by the development of open-{software, hardware} systems with donated hardware [5] and internetaccessible robot experiment platforms [6], [7]. This way, the same robotic system can be shared by a larger number of researchers and students, helping to dissolve the costs of purchasing and maintaining those systems.…”
Section: Introductionmentioning
confidence: 99%
“…The Robotarium [28] is a remote experimentation setup that focuses on swarm robotics. Also, the KUKA Robot Learning lab at KIT [29] offers the option to access a robotic lab with industrial robots over the internet. To the best of our knowledge, our benchmarking platform and the corresponding challenge provide the only remote and cloudbased scheme that focuses on robotic grasping and object rearrangement.…”
Section: Related Workmentioning
confidence: 99%
“…We would like to thank Tamim Asfour for his valuable input and helpful advice. All real-world experiments were performed at the KUKA Robot Learning Lab at KIT [23]. Special thanks to Wolfgang Wiedmeyer for his tremendous effort in building up the lab.…”
Section: Acknowledgmentmentioning
confidence: 99%